2021
DOI: 10.3389/fnmol.2021.682320
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Alleviates α-Synuclein Aggregation and Phosphorylation in Cellular Models of Synucleinopathy

Abstract: Parkinson’s disease (PD) is one of the most common neurodegenerative diseases. Pathologically, it is characterized by the aberrant aggregation of α-synuclein (α-syn) in neurons. Clinical evidence shows that patients with hypercholesterolemia are more likely to get PD, while lovastatin users have a lower risk of suffering from it. In this study, we investigated the effects of lovastatin on the aggregation and phosphorylation of α-syn in vitro. Our results demonstrate that α-syn preformed fibrils induce the phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…For example, some in vitro models have relied on further staining for phosphorylated Ser129 α-syn to analyze the formation of α-syn inclusions [8,16,17]. Additionally, some in vitro models have used PFF with liposomes to enhance internalization into cells [8,[18][19][20][21]. However, these models do not allow for the identification of the structures on the plasma membrane involved in PFF internalization or the PFF-induced signaling pathways because PFF are also internalized via receptormediated endocytosis [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some in vitro models have relied on further staining for phosphorylated Ser129 α-syn to analyze the formation of α-syn inclusions [8,16,17]. Additionally, some in vitro models have used PFF with liposomes to enhance internalization into cells [8,[18][19][20][21]. However, these models do not allow for the identification of the structures on the plasma membrane involved in PFF internalization or the PFF-induced signaling pathways because PFF are also internalized via receptormediated endocytosis [22].…”
Section: Resultsmentioning
confidence: 99%
“…However, these models do not allow for the identification of the structures on the plasma membrane involved in PFF internalization or the PFF-induced signaling pathways because PFF are also internalized via receptormediated endocytosis [22]. In some in vitro models, the number of cells with α-syn aggregation has been used as an index without further analysis [18][19][20][21]. These limitations highlight the need for more advanced in vitro model systems for high-throughput screening of α-syn propagation.…”
Section: Resultsmentioning
confidence: 99%
“…cDNAs corresponding to his-tagged α-syn and K80R mutant were cloned into a PRK172 plasmid and transformed into the E. coli BL21 DE3 strain. The expression and purification were performed as previously described (Dai et al, 2021). Briefly, the pellet from 1 L culture was resuspended in 100 ml osmotic shock buffer (30 mM Tris-HCl, 40% sucrose, and 2 mM EDTA, pH 7.2) and incubated for 10 min at room temperature.…”
Section: Protein Purificationmentioning
confidence: 99%
“…Commonly used lipid-lowering drugs such as Lovastatin, have shown an impact in decreasing motor symptom progression in patients with PD and they are beneficial for reducing the risk of PD [ 197 , 198 , 199 ]. A recent study showed that the underlying mechanism by which lovastatin mediates protective effects in PD is by inhibiting CK2 activity and decreasing pS129-αSyn [ 200 ].…”
Section: Ck2 In Other Neurodegenerative Disordersmentioning
confidence: 99%